Urinary Obstruction of Transplanted Kidney Caused by Uterine Adenomyosis and 2-Year Posthysterectomy Psoas Abscess in Conjunction with Transplanted Kidney - Yuta Takezawa; Yoshifumi Kadono; Takahiro Nohara; Atsushi Mizokami (Case Reports in Transplantation)
Urinary obstruction of the transplanted kidney caused by uterine leiomyoma is an extremely rare condition. To the best of our knowledge, there are only two reports in English literature. Psoas abscess secondary to renal graft pyelonephritis is also uncommon. We present this unusual case and its treatment course. A 43-year-old female presented with renal dysfunction. She was started on peritoneal dialysis from the age of 26 years and received kidney transplantation from her mother (living donor) at the age of 27 years. Computed tomography (CT) revealed right hydronephrosis and a large uterine mass compressing the distal ureter of the transplanted kidney. After a simple total hysterectomy, her renal function improved. Two years following the hysterectomy, she experienced painful urination, fever, right abdominal pain, and right lower limb pain. CT and T2-weighed magnetic resonance imaging of her pelvis demonstrated right psoas abscess in conjunction with transplanted kidney. She was treated with broad-spectrum antibiotics alone, which resulted in a good response. Urinary obstruction of the transplanted kidney caused by uterine leiomyoma is an extremely rare condition. Psoas abscess secondary to transplanted kidney pyelonephritis is also rare. We should keep these rare diseases in mind when treating such cases.